Social presence or physical presence? Determinants of purchasing behaviour in tourism live-streamed shopping. (October 2021) - Xu, Xueyan; Huang, Dan; Shang, Xinyu
Abstract: Travel live streaming has become an important tool for tourism marketers to attract and engage potential travellers, especially after the outbreak of Covid-19. Drawing on the presence theory, this study empirically explored the factors influencing consumers' purchasing behaviour in live-streamed shopping for tourism products. Data were collected manually from live-streamed events and analysed using multiple linear regressions. The results show that the physical presence factor effectively alleviates unsalable situations (i.e., circumstances where the product is not sold), while social presence by itself is not an adequate stimulus to greatly improved sales outcomes. Some basic features of live-streamed shopping such as the professionalism level of the platforms and the live-streaming anchors also play a role. The novel feature of this study is the understanding of the relationships between presence and customers' actual purchasing behaviour in tourism live-streamed shopping (TLSS). Highlights: All the presence factors work only on alleviating the unsalable situation. Physical presence significantly affects the number of unsalable products. Social presence alone does not have a significant impact on the sales outcome. Data were collected from a total of 306 real-time live-streaming events.